2018
DOI: 10.3390/md16050168
|View full text |Cite
|
Sign up to set email alerts
|

Precursor-Directed Generation of Indolocarbazoles with Topoisomerase IIα Inhibitory Activity

Abstract: One new indolocarbazole, 3-hydroxy-K252d (3), together with the recently reported 3-hydroxyholyrine A (1) and 3′-N-acetyl-3-hydroxyholyrine A (2), were obtained by feeding a culture of the marine-derived Streptomyces strain OUCMDZ-3118 with 5-hydroxy-l-tryptophan. Their structures were elucidated on the basis of spectroscopic analysis. Compound 1 potently induced apoptosis of gastric cancer cells by inhibiting topoisomerase IIα enzyme activity and reducing the expression of antiapoptosis protein level. Compoun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 19 publications
0
15
0
Order By: Relevance
“…This class of NPs have been found in many species, including fungi, invertebrates, and terrestrial and marine actinomyces, and have strong physiological activities and interesting chemical structures [91]. One new ICZ, 3-hydroxy-K252d 17 (Figure 6), was obtained by feeding a culture of the marine Streptomyces strain OUCMDZ-3118 with a precursor 5-hydroxy-L-tryptophan, along with previously reported compounds 3-hydroxyholyrine A 15 and 3 -N-acetyl-3-hydroxyholyrine A 16 [92]. The structure of 17 was confirmed by 2D NMR correlations.…”
Section: Precursor-directed Biosynthesismentioning
confidence: 81%
See 2 more Smart Citations
“…This class of NPs have been found in many species, including fungi, invertebrates, and terrestrial and marine actinomyces, and have strong physiological activities and interesting chemical structures [91]. One new ICZ, 3-hydroxy-K252d 17 (Figure 6), was obtained by feeding a culture of the marine Streptomyces strain OUCMDZ-3118 with a precursor 5-hydroxy-L-tryptophan, along with previously reported compounds 3-hydroxyholyrine A 15 and 3 -N-acetyl-3-hydroxyholyrine A 16 [92]. The structure of 17 was confirmed by 2D NMR correlations.…”
Section: Precursor-directed Biosynthesismentioning
confidence: 81%
“…The identity of the sugar moiety was determined to be l-rhamnose by gas chromatography-mass spectrometry (GC-MS) analysis of the acid hydrolysate of 17. Cytotoxicity tests showed that 17 had moderate toxicity against the human lung cancer cell line A549 and the human breast cancer cell line MCF-7, with IC 50 values of 1.2 µM and 1.6 µM, respectively [92].…”
Section: Precursor-directed Biosynthesismentioning
confidence: 99%
See 1 more Smart Citation
“…3-Hydroxyholyrine A (13, IC 50 : 0.51-7.2 µM, MTT assay), obtained by feeding a culture of the marine-derived Streptomyces strain OUCMDZ-3118 with 5-hydroxy-tryptophan, possessed broadspectrum activity against A549, MCF-7, K562, AGS, and MKN45 cancer cell lines. [50] The mechanistic investigations illustrated that 3-hydroxyholyrine A potently induced apoptosis of gastric cancer cells by inhibiting topoisomerase IIα enzyme activity and reducing the expression of antiapoptosis protein level.…”
Section: Indolocarbazole Alkaloidsmentioning
confidence: 99%
“…As part of our studies to search for new bioactive NPs from deep-sea-derived bacteria [ 33 , 34 , 35 ], we found that the extract of the fermentation broth of a deep-sea (2000 m) water-derived Ochrobactrum sp. OUCMDZ-2164 showed cytotoxic effect on the A549 (83% inhibition) and K562 (70% inhibition) cell line at 0.1 mg/mL.…”
Section: Introductionmentioning
confidence: 99%